Promoter methylation status of Ras-Association domain family member in pheochromocytoma - Richter, Antje Maria; Zimmermann, Tobias; Haag, Tanja; Walesch, Sara K.; Dammann, Reinhard Heinrich; Justus Liebig University Giessen (My University, 2015)
Pheochromocytomas (PCCs) are rare neuroendocrine tumors that arise from the medulla of the adrenal gland or the sympathetic ganglia and are characterized by the secretion of catecholamines. In 30 40% of patients, PCCs are genetically determined by susceptibility genes as various as RET, VHL, and NF1. We have analyzed the Ras-association domain family members (RASSFs) in PCCs regarding their inactivating promoter hypermethylation status. Previously, we reported a promoter methylation in PCC for the first family member RASSF1A. Promoter hypermethylation of CpG islands leads to the silencing of the according transcript and is a common mechanism for inactivation of tumor suppressors. In this study, we observed inactivating DNA modifications for the RASSF members RASSF2, RASSF5A, RASSF9, and RASSF10, but not for the members RASSF3, RASSF4, RASSF5C, RASSF6, RASSF7, and RASSF8. The degree of promoter methylation was 19% for RASSF2, 67% for RASSF5A, 18% for RASSF9, and 74% for RASSF10. Interestingly, the degree of hypermethylation for RASSF10 in hereditary PCCs was 89 vs. 60% in sporadic PCCs. A similar but less dramatic effect was observed in RASSF5A and RASSF9. Including all RASSF members, we found that of 25 PCCs, 92% show promoter methylation in at least in one RASSF member. In 75% of the hereditary PCC samples, we found two or more methylated RASSF promoters, whereas in sporadic PCCs only 46% were observed. In summary, we could show that in PCC several RASSF members are strongly hypermethylated in their promoter regions and methylation of more than one RASSF member occurs in the majority of PCCs. This adds the inactivation of genes of the RASSF tumor suppressor family to the already known deregulated genes of PCC.
Keywords: pheochromocytoma; tumor suppressor; DNA methylation; epigenetics; RASSF; ddc:570